KEPEMIMPINAN PEREMPUAN DALAM PERSPEKTIF PENGELOLAAN LEMBAGA PENDIDIKAN ISLAM - Nguyun Akmala; Muhammad Al-Fatih (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study examines the role of women in leadership within the management of Islamic educational institutions, specifically at Pondok Pesantren Salafiyah Syafi’iyah Seblak. The background of this research is based on the increasing involvement of women as leaders in the field of education, despite facing various challenges such as gender stereotypes and limited support from related institutions.The research employs a qualitative approach using a case study method, with data collected through observation, interviews, and documentation. The findings reveal that Mrs. Nyai Nur Laili Rohmah applies a democratic and open leadership style that prioritizes participation. Moreover, she successfully integrates classical management functions—planning, organizing, implementing, and supervising—with Islamic spiritual and moral values.Mrs. Nyai’s leadership fosters an educational environment that is religious, inclusive, and orderly, while also demonstrating that women possess equal ability and competence as men in managing educational institutions. This study underscores the importance of supporting gender equality and strengthening women’s capacities so they can contribute optimally to the management of Islamic education.